Performance of exotic cultivars of gerbera (Gerbera jamesonii) under low cost naturally ventilated greenhouse environment - SINGH, KRISHAN P; MANDHAR, S C (The Indian Journal of Agricultural Sciences, 2014)
The performance of 9 exotic cuitivars of gerbera, viz Diablo, Lyonella, Omelia, Sunset, Tara, Thalassa, Tiramisu, Twiggy and Whitsun was studied under lowcost naturally ventilated greenhouse environment. Cultivar Lyonella recorded maximum height of plant (53.49 cm), spread of plant (72.71 cm) and number of suckers (4.55) and leaves (46.66 ) per plant. Survival percentage of plants up to one year of planting did not differ significantly and varied from 86.11 % in case of cultivar Whitsun and 100 % in case of cultivars Omelia and Twiggy. The earliest (38.22 and 51.13 days) and latest (86.66 and 94.74 days) flowering were observed in cultivars Whitsun and Tiramisu, respectively. The maximum flower diameter (10.44 cm), stalk length (64.00 cm), stalk thickness (0.75 cm diameter) and fresh weight of stalk (23.01 g) were recorded in cultivars Thalassa, Lyonella, Tiramisu and Omelia, respectively. Higher yield (number) of flowers per plot and per plant per year was obtained in Diablo (1 223.33 and 54.67) followed by Lyonella (1 092.33 and 47.76), Omelia (1 073.66 and 46.28) and Thalassa (1 067.00 and 46.26) and the minimum in cultivar Tara (501.66 and 21.60.). The highest 1st grade (96.42%) and lowest lInd grade (3.32%) and IIIrd grade/unmarketable (0.25%) flowers were recorded in cultivar Twiggy, followed by Sunset (94.36%, 5.13% and 0.49% respectively), Tiramisu (92.70%, 6.83% and 0.45% respectively) and Lyonella (92.69%, 6.48% and 0.64% respectively). The lowest 1st grade flowers (79.81%) and the highest unmarketable Dowers (12.51%) were obtained in cultivar Whitsun. The temperature inside the greenhouse varied from 28°C to 36.9°C and the temperature build-up could be controlled from 1.1°C to 3°C. The retative humidity indside the greenhouse varied from 24 to 70% when outside relative humidity varied from 20 to 70%.